Shattering one-way mirrors – data subject access rights in practice - Ausloos, Jef; Dewitte, Pierre (International data privacy law, 2018)
EU data protection law offers individuals an arsenal of rights they can exercise against controllers. Among them, the right of access constitutes a cornerstone of data subjects’ informational empowerment. The right allows individuals to monitor what personal data are held about them, how it is being processed and with whom it is shared. Especially in light of a growingly complex data processing eco-system and the increased reliance on ‘data’ to make all kinds of (life-affecting) decisions, the right of access can play a crucial role in safeguarding fairness, accountability, and responsibility. All the more considering the one-way mirrors many controllers have erected around them. Indeed, the right of access offers an effective opportunity to break through information asymmetries so prevalent in the context of information society services today. In practice, however, the right of access—and data subject rights more broadly—is/are often said to be ignored, inefficient, underused and/or obsolete. Nevertheless, not much empirical research exists actually substantiating these claims. Anecdotal evidence does suggest some truth to the former three allegations,1 but concluding therefore that (some) data subject rights are obsolete seems unwarranted. In order to have an informed debate—grounded in practical reality—we set out to gather empirical data on how data subject rights are exercised and accommodated in the field.